Surge protective device for low voltage equipment. - Ab Kadir, Mohd Zainal Abidin; Rameli, Norhidayu; Mohd Ariffen, Amizah; Gomes, Chandima; Wan Ahmad, Wan Fatinhamamah; Jasni, Jasronita (2011)
The present invention discloses a surge protecting device (50) for low voltage equipment (single phase loads) that has two stages (4, 5) of protection which include a voltage limiting stage (5) and a current diverting/dissipater stage (4) that serves to ground the trailing edge of the transient surge current. It is in essence a three line surge protector (50) comprising of a plurality of metal oxide varistors (MOVs) (10) and a plurality of avalanche zener diodes (20), wherein a predefined number of individual MOVs (10) are connected in parallel, the combination of parallel connected MOVs (10) forming a current diverting element (1, 2, 3) such that an individual current diverting element (1, 2, 3) is connected between the live and neutral lines, live and ground lines and the neutral and ground lines respectively. Similarly a pair of zener-diodes (20) of the plurality of zener-diodes (20) are connected such that, the cathodes of the diodes (20) face each other in opposition and the anodes face way from each other to thus form a zener-regulator unit (6, 7, 8). The zener-regulators (6, 7, 8) thus formed are connected between the live and neutral lines, live and ground lines and the neutral and ground lines respectively. The low voltage surge protective device (50) of the present invention is a Class III surge protective device (50) designed in accordance with the MS IEC 61643-1 standard.